Analysis of publications on problem solving methodology and themes in the initial training of chemistry teachers (Research, Society and Development, 2020)
This work presents a bibliographic research in national and international journals in the area of Science Teaching, covering the period from 2007 to 2018, for which we propose to investigate and understand how the articulation of themes and methodology of Science Resolution has been approached. Problems in the initial formation of chemistry teachers. Additionally, it seeks to identify the relationships established between the proposed themes and the methodological strategy of Problem Solving in the different curricular components, as well as the pedagogical, formative and reflexive aspects developed at this level of education. In addition, we examine the types of themes and problems flagged in the literature. The analysis of the results shows a variety of approaches that address these methodological perspectives in Higher Education, as well as pointing to evidence on the development of skills and competences suggested in the normative documents for the professional formation of the teaching career.